Infection with the Avian Coronavirus: A recurring problem in turkeys - Mohamed Houta; Olusegun Awe; Ahmed Ali (German Journal of Veterinary Research)
Turkey coronavirus (TCoV) is a Gammacoronavirus causing acute contagious enteritis in young turkeys, leading to impaired growth, low feed conversion, and increased mortality. The TCoV infections, in association/combination with other enteropathogenic viruses, bacteria & protozoa, are associated with poult enteritis-mortality syndrome (PEMS) in turkeys of 1-4 weeks age. In this review, classification & genotyping of TCoV, the implications of its recombination, and challenges to develop efficient vaccines against it are discussed. Though TCoV is monophyletic with infectious bronchitis virus (IBV) with a sequence similarity of ≥86, however a classification scheme gathering all avian coronaviruses (ACoVs) is not established. Based on the N gene, ACoVs are classified into five clades. Clades 1 & 2 (chickens), Clade 3 (pigeon) Clade 4 (duck), and Clade 5 (goose). The Spike (S) gene of ACoVs has shown exceptional lability of being easily switched with multiple recombination events suggesting that TCoV may be an IBV recombinant. Recombination events altered the pathogenicity, host specificity, and tissue tropism of TCoVs. Attempts to develop attenuated, inactivated, DNA, and virus-vectored vaccines are ongoing. Experimentally, the attenuated TCoV strains induced strong humoral and cellular immune responses and completely protected against the homologous challenge but not heterologous TCoV challenge. Meanwhile, genetically engineered vaccines, either DNA or virus vectored vaccines, are limited with either late induction of a protective immune response and/or inability of the elicited antibody to neutralize virus infection and protect against virus challenge. Future research should focus on improving vaccine efficiency against TCoVs by developing more immunogenic vaccines, determining the appropriate dosing regimens, and include potent adjuvants